2017
DOI: 10.1007/s13399-017-0294-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous catalytic depolymerisation and conversion of industrial kraft lignin into low-molecular-weight aromatics

Abstract: Base-catalysed depolymerisation of lignin using sodium hydroxide has been shown to be an effective approach towards exploiting industrial (technical) lignins within the pulp and paper industry. In the present work, a pine kraft lignin (Indulin AT) which is precipitated from black liquor of linerboard-grade pulp was depolymerised via base catalysis to produce lowmolecular-mass aromatics without any organic solvent/capping agent in a continuous-flow reactor setup for the first time. The catalytic conversion of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 34 publications
(53 reference statements)
3
48
0
Order By: Relevance
“…Various lignin depolymerisation and conversion methods have been described in the literature, each approach having its own advantages and limitations. Examples comprise acidcatalysed [11,12], base-catalysed [13,14], thermochemical [15,16], biochemical [1,17], reductive [18,19] and oxidative [20][21][22] lignin depolymerisation. Oxidative depolymerisation, in particular, emerges as a promising route among the deconstruction strategies, as it can produce highly functionalised chemicals under relatively mild operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various lignin depolymerisation and conversion methods have been described in the literature, each approach having its own advantages and limitations. Examples comprise acidcatalysed [11,12], base-catalysed [13,14], thermochemical [15,16], biochemical [1,17], reductive [18,19] and oxidative [20][21][22] lignin depolymerisation. Oxidative depolymerisation, in particular, emerges as a promising route among the deconstruction strategies, as it can produce highly functionalised chemicals under relatively mild operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of high molecular weight insoluble structures and char is the consequence of the repolymerization that occurs. In order to suppress repolymerization, we have developed a novel continuous flow reactor (CFR) to depolymerize ‘Indulin AT’ (a commericial Kraft lignin that was precipitated from the black liquor of softwood pulp) at 170–240 °C for 1–4 min of residence time by using NaOH as a catalyst [18]. We found that, under the experimental conditions, some of the Indulin AT macromolecules were depolymerized into LMMC.…”
Section: Introductionmentioning
confidence: 99%
“…All the investigations have been performed systematically using the same reference conditions (350°C, 25 MPa, 5.5 wt% lignin, 4 wt% phenol, and 1.6 wt% potassium carbonate). The influence of temperature was investigated in five steps from 290 to 370°C [19] and showed that the yield of bio-oil decreased slightly when the temperature was increased. The yield of water-soluble organics (WSO) as well as the char on catalyst increased slightly.…”
mentioning
confidence: 99%